DPP containing D–π–A organic dyes toward highly efficient dye-sensitized solar cells. (February 2016) - Chiu, Kuo Yuan; Govindan, Venkatesan; Lin, Ling-Chuan; Huang, Shin-Han; Hu, Jia-Cheng; Lee, Kun-Mu; Gavin Tsai, Hui-Hsu; Chang, Sheng-Hsiung; Wu, Chun-Guey
Abstract: Two diketopyrrolopyrrole (DPP) containing D–π–A organic dyes, named as TEDBn and TEDTh were prepared. Their optical, electrochemical and photophysical properties were investigated and their application in dye-sensitized solar cells (DSCs) was demonstrated. The broaden absorption and low-energy λ max of DPP containing dyes were contributed from DPP bridge and EDOT π-conjugated moiety. Compared to TEDTh, TEDBn has smaller absorption coefficient and higher optical bandgap. Nevertheless the power conversion efficiency (PCE) of TEDBn based DSC is 7.2% which is larger than that of TEDTh based DSC and 90% of N719 based cell. The higher PCE of TEDBn based device originates from both higher open-circuit voltage (VOC ) and short-circuit current (JSC ). Femtosecond time-resolved photoluminescence data show that the electron injection at TEDBn/TiO2 is more efficient than that at TEDTh/TiO2 interface, resulting in higher JSC (and IPCE) of TEDBn based DSC. Density function theory (DFT) calculations revealed that TEDBn is a linear structure which leads to higher dye loading on TiO2 than TEDTh which featured a bend conformation, better TiO2 surface coverage, resulting in larger VOC . Therefore, the overall efficiency of the cell sensitized by TEDBn is better than that the devices based on TEDTh. Graphical abstract: Two diketopyrrolopyrrole (DPP) containing D–π–A organic dyes, TEDBn and TEDTh were prepared for using in DSC. The differences between TEDBn and TEDTh were carefully explored experimentally and theoretically and the reasons for the good photovoltaic performance of TEDBn were clearly identified. Highlights: Two DPP containing D–π–A organic dyes, TEDBn and TEDTh were prepared. The differences between TEDBn and TEDTh were explored in detail. The application of TEDBn and TEDTh in DSC was investigated.